Chapter Un'educazione all'umano. Letteratura e ideologia in Claudio Magris - Fastelli, Federico (Biblioteca di Studi di Filologia Moderna, 2021)
The essay discusses Magris' idea of literature through his theoretical interventions. In particular, it addresses the crucial issue in the writer's work, concerning the complex relationship between political commitment and artistic activity. The result is a surprising reflection on the ideological function of literary texts and on the tasks of the writer in the contemporary world.